Boundary Layer of a Dusty Fluid Flow Over A Stretching Sheet - S, Noorzehan F. M.; A, Anati; M, Syahira; M, Radiah; J, Nurul A. (International Journal of Engineering and Technology, 2018)
A numerical analysis has been carried out to investigate the effects of suction parameter and fluid-particle interaction parameter on boundary layer of dusty fluid towards the stretching sheet. The governing equations of boundary layer were transformed into system of coupled non-linear ordinary differential equations with the help of similarity transformation. The transformed equations then solved numerically using bvp4c solver of MATLAB software. The effects of physical parameters on velocity profile of fluid phase and dust particle phase were obtained and analysed through several plots. Useful discussion were carried out with the help of plotted graphs and tables. The numerical results obtain were compared and found to be in good agreement with the previous study. It is observed that the presence of suction increase the velocity of fluid meanwhile opposite with velocity of particle. Besides that, the fluid-particle interaction parameter increase the velocity of particle. These findings will be used for future studies involving nanofluid.